Anatomical, biochemical and transcriptome analyses of Vitis vinifera cv. 'Hongju' reveal novel information regarding the seed hardness of stenospermocarpic soft‐seed grapes. (4th December 2019) - Yim, Bomi; Mun, Jeong‐Hwan; Park, Soo Hyun; Shim, Hye Rim; Kim, Jun‐Hyuk; Hur, Youn Young; Yu, Hee‐Ju
Abstract: The breeding of new stenospermocarpic seedless grape cultivars is of particular importance to the growing table grape market and grape processing industry. However, the developmental and genetic architectures of soft‐seed and seedlessness traits are unclear. In this study, we performed anatomical, histochemical and gene expression analyses to characterize the morphological and genetic basis of the seed hardness of 'Hongju', a stenospermocarpic soft‐seed grape cultivar developed by crossbreeding maternal 'Italia' and paternal 'Perlon' cultivars. We found intensively lignified medium integument layers in the seeds of hard‐seed cultivars, but these layers were degraded in the stenospermocarpic seedless cultivars beginning 35 days after flowering. The expression of genes related to the lignin and cellulose biosynthesis pathways was downregulated, whereas that of several cell‐wall loosening‐related genes was upregulated in 'Hongju' compared with 'Italia' beginning at 21 days after flowering. These results suggest that transcriptional suppression of the lignin and cellulose biosynthesis pathways coupled with reduced formation of medium integument plays an important role in the development of soft seeds in stenospermocarpic seedless grape cultivars.